1992
DOI: 10.1111/j.1471-4159.1992.tb11356.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Elastase as a Secretory Protease from Cultured Rat Microglia

Abstract: In the course of studying the secretory products of microglia, we detected protease activity in the conditioned medium. Various proteins (casein, histone, myelin basic protein, and extracellular matrix) were digested. The protease activity was characterized by using purified myelin basic protein as a substrate. Maximal activity was observed at neutral pH levels (7-8), which was different from the optimum pH level of proteolytic activity observed in the cell homogenate. The activity was inhibited approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 46 publications
1
87
0
1
Order By: Relevance
“…In vivo imaging techniques revealed that the activation of the P2Y 12 receptor was required to extend the processes toward a lesion site in damaged brain tissue [2,9]. These studies indicate the prominent role of P2Y 12 receptor activation in microglial motility. We also reported that P2Y 6 receptor activation stimulated by its ligand uridine 5′-diphosphate (UDP) induced dynamic cytoskeletal arrangement and process movement in microglia, resulting in increase of microsphere phagocytosis [1].…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…In vivo imaging techniques revealed that the activation of the P2Y 12 receptor was required to extend the processes toward a lesion site in damaged brain tissue [2,9]. These studies indicate the prominent role of P2Y 12 receptor activation in microglial motility. We also reported that P2Y 6 receptor activation stimulated by its ligand uridine 5′-diphosphate (UDP) induced dynamic cytoskeletal arrangement and process movement in microglia, resulting in increase of microsphere phagocytosis [1].…”
Section: Introductionmentioning
confidence: 81%
“…Activation of the P2Y 12 receptor also causes integrin-dependent microglial process extension [8]. In vivo imaging techniques revealed that the activation of the P2Y 12 receptor was required to extend the processes toward a lesion site in damaged brain tissue [2,9]. These studies indicate the prominent role of P2Y 12 receptor activation in microglial motility.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Mouse primary cultured microglia were prepared as described previously [5,35]. Briefly, a mixed glial culture was prepared from neonatal IRF8 knockout, hetero-knockout, and wildtype mice and maintained for 10-16 days in DMEM with 10 % fetal bovine serum [5,36].…”
Section: Microglial Culturementioning
confidence: 99%